Headache in an Obese Adolescent Male: A Nonclassical Presentation of an Uncommon Disease - Bill Zhou BS; Catherine Yim MD; Soni Chawla MD (SAGE Publishing, 2018)
Background . Idiopathic intracranial hypertension (IIH), also known as pseudotumor cerebri, is a diagnosis of exclusion in the clinical scenario of increased intracranial pressure without an identifiable cause. This case report provides a brief review of current literature on IIH, important differential considerations to rule out prior to diagnosis, and relevant imaging findings of IIH. Case Presentation . An 18-year-old male presenting with headache and blurry vision was found to have signs of increased intracranial pressure on imaging without other abnormalities to explain the cause, suggesting IIH as a diagnosis. Conclusion . IIH is classically seen in overweight females of childbearing age but should be considered in all obese patients, including the pediatric population given the increasing rate of childhood obesity.